Digital empowerment in agriculture: Fostering climate resilience and restoration with smart solutions for smallholder farmers. Open Geospatial Consortium Innovation Days Europe 2024 - Eitzinger, Anton (2024)
Digital technology has the potential to empower farmers by integrating them into information flow and data ecosystems. This not only enhances their autonomy with access to tailored agricultural advice and knowledge, but also tackles climate change and biodiversity loss through actionable resilience and restoration strategies. However, challenges for the ongoing digital transformation in agriculture remain for the near future, including limited connectivity in many areas, digital literacy issues, and the need for more farmer-centered designs and interoperability of digital innovations. We will showcase successful initiatives like digital climate advisory services in Africa and Latin America, a community-led digital platform for on-farm tree restoration MyFarmTrees, and Croppie as a AI-supported coffee yield estimation approach, among others.